Evaluation of optimal medical therapy in acute myocardial infarction patients with prior stroke - Dongfeng Zhang; Xiantao Song; Sergio Raposeiras-Roubín; Emad Abu-Assi; Jose Paulo Simao Henriques; Fabrizio D'Ascenzo; Jorge Saucedo; José Ramón González-Juanatey; Stephen B. Wilton; Wouter J. Kikkert; Iván Nuñez-Gil; Albert Ariza-Sole; et al. (SAGE Publishing, 2021)
Background: Treatment of acute myocardial infarction (AMI) patients with prior stroke is a common clinical dilemma. Currently, the application of optimal medical therapy (OMT) and its impact on clinical outcomes are not clear in this patient population. Methods: We retrieved 765 AMI patients with prior stroke who underwent percutaneous coronary intervention (PCI) during the index hospitalization from the international multicenter BleeMACS registry. All of the subjects were divided into two groups based on the prescription they were given prior to discharge. Baseline characteristics and procedural variables were compared between the OMT and non-OMT groups. Mortality, re-AMI, major adverse cardiovascular events (MACE), and bleeding were followed-up for 1 year. Results: Approximately 5% of all patients presenting with AMI were admitted to the hospital for ischemic stroke. Although the prescription rate of each OMT medication was reasonably high (73.3%-97.3%), 47.7% lacked at least one OMT medication. Patients receiving OMT showed a significantly decreased occurrence of mortality (4.5% vs 15.1%, p  < 0.001), re-AMI (4.2% vs 9.3%, p  = 0.004), and the composite endpoint of death/re-AMI (8.6% vs 20.5%, p  < 0.001) compared to those without OMT. No significant difference was observed between the groups regarding bleeding. After adjusting for confounding factors, OMT was the independent protective factor of 1-year mortality, while age was the independent risk factors. Conclusions: OMT at discharge was associated with a significantly lower 1-year mortality of patients with AMI and prior stroke in clinical practice. However, OMT was provided to just half of the eligible patients, leaving room for substantial improvement. Clinical Trial Registration: NCT02466854